Penerapan Sanksi Serta Pengawasan Terhadap Kode Etik Notaris Oleh Dewan Kehormatan - Yurist Firdaus Muhammad; Budi Santoso (Notarius, 2023)
AbstractNotary is a profession that provides legal services to the public. They need to be monitored by a neutral institution so that the quality of the notary work remains good. This supervision is important to improve the ability of all notaries in carrying out their duties. According to 87 articles of the Notary Rules, oversight of the Notary Rules may be carried out by the Honorary Council. This research aims to determine the role of the honorary council in supervising and enforcing the notary’s ethics code, as well as the role of the honorary council in applying punishmentss to notaries who violate the ethics. The research method used is normative juridical. Based on this study, it is concluded that: 1).The supervision and guidance of the Honorary Council aims to improve the quality of the notary's work ethic in the performance of the notary's task in accordance with the provisions of the Code of Ethics. 2).Notaries who violate the Ethics may be sanctioned by the Honorary Council such as: a).Reprimand; b).Warning; c).Temporary suspension from membership of the Association; d).Dismissal with honor from the Association; also e).Disrespectful dismissal from the Association's membership.Keywords: supervision; the code; notaryAbstrakNotaris adalah profesi yang memberikan layanan hukum kepada masyarakat. Mereka perlu diawasi oleh lembaga netral agar kualitas kerja notaris tetap baik. Pengawasan ini penting untuk meningkatkan kemampuan semua notaris dalam menjalankan tugas mereka. Menurut Pasal 7 Kode Etik Notaris, pengawasan Kode Etik Notaris dapat dikerjakan oleh Dewan Kehormatan. Penelitian ini bertujuan untuk mengetahui bagaimana dewan kehormatan dalam menjalankan peran mengawasi dan menegakkan kode etik notaris, serta perannya dalam menerapkan hukuman kepada notaris yang melanggar kode etik. Metode penelitian yang digunakan adalah yuridis normatif. Berdasarkan hasil penelitian ini, diketahui bahwa: 1) pengawasan dan pembinaan oleh dewan kehormatan bertujuan untuk meningkatkan kualitas etika kerja notaris dalam menjalankan tugas sesuai dengan ketentuan kode etik. 2) notaris yang melanggar kode etik dapat dijatuhi sanksi oleh dewan kehormatan berupa: a) teguran; b) peringatan; c) pemberhentian sementara dari keanggotaan asosiasi; d) diberhentikan dengan hormat dari keanggotaan asosiasi; dan e) diberhentikan dengan tidak hormat dari keanggotaan asosiasi.Kata kunci: pengawasan; kode etik; notaris.